2022
DOI: 10.20343/teachlearninqu.10.16
|View full text |Cite
|
Sign up to set email alerts
|

Do Young People Really Know How to Collaborate for Common Success? Study on Undergraduate Students’ Perception of Collaborative Work in a Spanish University

Abstract: This paper studies undergraduate student attitudes towards team-based projects, connecting those attitudes to challenges and overall perception of this work. This study was conducted with 220 students in the context of three subjects taught at a Spanish University, that included collaborative projects as mandatory assignments to be developed over the course of the subject. The instrument was a Likert scale-based questionnaire. As a methodology, the Rasch model was used, making it possible to apply indirect mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study of [44] also confirmed that the lack of clear guidelines and expectations during collaborative tasks among undergraduate students is a problem. This is also supported by the argument of [45] that the way collaborative work is usually planned is not very effective among university students. Therefore, no implementation of clear guidelines promotes conflicts and establishes a foundation for ineffective collaboration, disintegrating team members against working towards shared objectives.…”
Section: Question 1 Theme 2: Lack Of Clear Guidelines and Expectationsmentioning
confidence: 77%
“…The study of [44] also confirmed that the lack of clear guidelines and expectations during collaborative tasks among undergraduate students is a problem. This is also supported by the argument of [45] that the way collaborative work is usually planned is not very effective among university students. Therefore, no implementation of clear guidelines promotes conflicts and establishes a foundation for ineffective collaboration, disintegrating team members against working towards shared objectives.…”
Section: Question 1 Theme 2: Lack Of Clear Guidelines and Expectationsmentioning
confidence: 77%